Pivotal role of connective tissue growth factor in lung fibrosis: MAPK-dependent transcriptional activation of type I collagen. - Ponticos, M; Holmes, A; Shi-wen, X; Leoni, P; Khan, K; Rajkumar, V; Hoyles, R; Bou-Gharios, G; Black, C; Denton, C; Abraham, D; Leask, A; et al. (2009)
OBJECTIVE: Connective tissue growth factor (CTGF; CCN2) is overexpressed in systemic sclerosis (SSc) and has been hypothesized to be a key mediator of the pulmonary fibrosis frequently observed in this disease. CTGF is induced by transforming growth factor beta (TGFbeta) and is a mediator of some profibrotic effects of TGFbeta in vitro. This study was undertaken to investigate the role of CTGF in enhanced expression of type I collagen in bleomycin-induced lung fibrosis, and to delineate the mechanisms of action underlying the effects of CTGF on Col1a2 (collagen gene type I alpha2) in this mouse model and in human pulmonary fibroblasts. METHODS: Transgenic mice that were carrying luciferase and beta-galactosidase reporter genes driven by the Col1a2 enhancer/promoter and the CTGF promoter, respectively, were injected with bleomycin to induce lung fibrosis (or saline as control), and the extracted pulmonary fibroblasts were incubated with CTGF blocking agents. In vitro, transient transfection, promoter/reporter constructs, and electrophoretic mobility shift assays were used to determine the mechanisms of action of CTGF in pulmonary fibroblasts. RESULTS: In the mouse lung tissue, CTGF expression and promoter activity peaked 1 week after bleomycin challenge, whereas type I collagen expression and Col1a2 promoter activity peaked 2 weeks postchallenge. Fibroblasts isolated from the mouse lungs 14 days after bleomycin treatment retained a profibrotic expression pattern, characterized by greatly elevated levels of type I collagen and CTGF protein and increased promoter activity. In vitro, inhibition of CTGF by specific small interfering RNA and neutralizing antibodies reduced the collagen protein expression and Col1a2 promoter activity. Moreover, in vivo, anti-CTGF antibodies applied after bleomycin challenge significantly reduced the Col1a2 promoter activity by approximately 25%. The enhanced Col1a2 promoter activity in fibroblasts from bleomycin-treated lungs was partly dependent on Smad signaling, whereas CTGF acted on the Col1a2 promoter by a mechanism that was independent of the Smad binding site, but was, instead, dependent on the ERK-1/2 and JNK MAPK pathways. The CTGF effect was mapped to the proximal promoter region surrounding the inverted CCAAT box, possibly involving CREB and c-Jun. In human lung fibroblasts, the human COL1A2 promoter responded in a similar manner, and the mechanisms of action also involved ERK-1/2 and JNK signaling. CONCLUSION: Our results clearly define a direct profibrotic effect of CTGF and demonstrate its contribution to lung fibrosis through transcriptional activation of Col1a2. Blocking strategies revealed the signaling mechanisms involved. These findings show CTGF to be a rational target for therapy in fibrotic diseases such as SSc.